Surgical Treatment and Survival in Patients with Liver Metastases from Neuroendocrine Tumors: A Meta-Analysis of Observational Studies - Bacchetti, Stefano (Hindawi Publishing Corporation, 2013)
Introduction. The role of hepatic resection in patients with liver metastases from gastroenteropancreatic neuroendocrine tumors (GEP-NETs) is still poorly defined. Therefore, we examined the results obtained with surgical resection and other locoregional or systemic therapies by reviewing the recent literature on this topic. We performed the meta-analysis for comparing surgical resection of hepatic metastases with other treatments. Materials and Methods. In this systematic review and meta-analysis of observational studies, the literature search was undertaken between 1990 and 2012 looking for studies evaluating the different survivals between patients treated with surgical resection of hepatic metastases and with other surgical or nonsurgical therapies. The studies were evaluated for quality, publication bias, and heterogeneity. Pooled hazard ratio (HR) estimates and 95% confidence intervals (CI.95) were calculated using fixed-effects model. Results. We selected six studies in the review, five of which were suitable for meta-analysis. We found a significant longer survival in patients treated with hepatic resection than embolisation HR 0.34 (CI.95 0.21–0.55) or all other nonsurgical treatments HR 0.45 (CI.95 0.34–0.60). Only one study compared surgical resection with liver transplantation and meta-analysis was not feasible. Conclusions. Our meta-analysis provides evidence supporting the hypothesis that hepatic resection increases overall survival in patients with liver metastases from GEP-NETs. Further randomized clinical trials are needed to confirm these findings and it would be desirable to identify new markers to properly select patients for surgical treatment.